THE RELATION BETWEEN MICROFINANCE CREDIT (KREDIT USAHA RAKYAT) AND THE FINANCIAL PERFORMANCE ON SMALL AND MEDIUM ENTERPRISE IN MANADO, NORTH SULAWESI - Balak, Vanesa Anastasia; Tumiwa, Johan . (Universitas Sam Ratulangi, 2018)
Abstract: Manado city's economy is largely contributed through the role of SMEs in mobilizing economic activities in various fields, capital limitations are a source of business development problems and lack of innovation in busines .The government together with the cooperative service and SMEs are trying to facilitate SMEs to get microfinance credit funds. This study aimed to see whether there are differences in financial performance on the financial ratio analysis based on financial ratio, of 9 Small Medium Enterprises before and after using funds microfinance credit in manado. Based on the results shows that the financial performance of SMEs in Manado City from the year before using microfinance credit and after using microfinance credit is changin, which is the average value of the financial ratio analysis experienced good changes. SMEs should be more effective in utilizing existing resources to generate sales, and SMEs should know the condition of the companys financial performance in their business from time to time so that the future can anticipate and quickly taking decisions for possibilities that could happen in the future, and to further improve the companys performance in the future.Keywords: microfinance credit, financial performance, small and medium enterprises.